Rice cultivation ambition in the new and updated Nationally Determined Contributions: 2020-2021: Analysis of agricultural sub-sectors in countries’ climate change strategies - Trang, Vu H; Nelson, Katherine M.; Rose, Sabrina; Khatri-Chhetri, Arun; Wollenberg, Eva Karoline; Sander, Björn Ole (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The share of countries that referenced rice cultivation actions in new and updated NDCs has increased since the previous round of NDCs.